Cognitive hardiness in the New Zealand military - Carston M; Gardner D (New Zealand Psychological Society, 2009)
The current research investigated appraisal, coping, cognitive hardiness and work related stress in 439 military personnel. Associations were found between challenge appraisals, adaptive coping and positive psychological and physical outcomes. Associations were also found between threat appraisals, maladaptive coping and negative psychological and physical outcomes. Cognitive hardiness was not found to be associated with building adaptive coping strategies and did not mediate the positive pathway to stress. However, cognitive hardiness did mediate the negative pathway suggesting a potential protective element to this construct.
Keywords: 1701 Psychology; 1702 Cognitive Sciences